THE PERCEPTION OF STUDENTS ON THE POLITICAL RIGHTS OF MALAYSIAN YOUTH TO PARTICIPATE IN POLITICS - Muhammad Danish Fahmi, Muhammad Sufian (Universiti Malaysia Sarawak (UNIMAS), 2022)
The issue of political right is a major concern for every country in the world, particularly for young people who are interested in politics. The participation of young people in politics in Malaysia is increasing and changing and this is a positive development. They have the ability and the right to join political parties and to contribute to the national political strength of the country. This is a result of the implementation of "VOTE 18," which encourages young people to participate in politics. This is a catalyst for the rise of young people in politics, and it is important that young people themselves understand their role in this situation. The purpose of this paper is to discuss the perceptions of students on the political rights of Malaysian youth to participate in political life. The purpose of this study is to determine the best way to focus on the involvement of young people in Malaysian politics as well as student perceptions of the current political situation.